Advanced computing in industrial mathematics : 12th annual meeting of the Bulgarian section of SIAM December 20-22, 2017, Sofia, Bulgaria revised selected papers /: 12th annual meeting of the Bulgarian section of SIAM December 20-22, 2017, Sofia, Bulgaria revised selected papers. ([2019]) - Unknown
No abstract available